2015
DOI: 10.4103/0975-7406.163456
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence based diagnostic techniques for oral cancer

Abstract: Oral cancer is one of the most common cancers worldwide. Despite of various advancements in the treatment modalities, oral cancer mortalities are more, particularly in developing countries like India. This is mainly due to the delay in diagnosis of oral cancer. Delay in diagnosis greatly reduces prognosis of the treatment and also cause increased morbidity and mortality rates. Early diagnosis plays a key role in effective management of oral cancer. A rapid diagnostic technique can greatly aid in the early diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…MFs are characterized by actin microfilament bundles (stress fibers) containing smooth muscle α-actin, thus presenting high contractile capacity ( 15 ). MFs are transdifferentiated fibroblasts and the beta growth transforming factor (TGF-β) cytokine plays an important role in directly promoting their development by inducing α-SMA expression ( 10 , 16 - 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFs are characterized by actin microfilament bundles (stress fibers) containing smooth muscle α-actin, thus presenting high contractile capacity ( 15 ). MFs are transdifferentiated fibroblasts and the beta growth transforming factor (TGF-β) cytokine plays an important role in directly promoting their development by inducing α-SMA expression ( 10 , 16 - 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential correlations between the angiogenic index and the presence of MF in RC and RRC were also evaluated, only detected in RRC, corroborating another study ( 17 ), which found a positive and moderate correlation between these indices in RRC. In the case of odontogenic lesions, the presence of MF constitutes a source of angiogenic proteins, as well as extracellular matrix degradation proteinases, which together favor lesion growth ( 10 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…While traditional intraoral cameras with violet or blue light sources employ orange filters, devices designed to assess green fluorescence of soft tissues, such as the VELscope (LED Dental, Atlanta, GA, USA) employ filters to remove the excitation light (in this instance, 400–460 nm) . The results of the present study show the potential value of a selective green filter stack when used with violet or blue light to assess green fluorescence of tooth structure.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, QD-based nanoprobes can ensure better sensitivity when used in combination with imaging techniques 14 , 29 . This characteristic is essential for the analysis of tumour tissues, which display alterations in the concentration and constitution of extra- and intracellular components, such as collagen, elastin, keratin, haemoglobin, and NADPH, leading in some cases to substantial autofluorescence 30 .…”
Section: Discussionmentioning
confidence: 99%